Protocolo de Avaliação Comportamental Precoce: acompanhando crianças fora de risco de TEA - Sarilho, Cláudio Almeida (2020)
The ASD tracking instruments have different strategies to collect information about child development, using verbal reports or homemade videos. However, observing the child's behavior in structured tasks is the most reliable strategy to reach this data. The cohort design is the most recommended one to investigate the ASD risk, and, in order to apply it, it is necessary to follow two groups over time: one is exposed to the risk of the disorder; and the other is not exposed to it. This study aimed to analyze the protocol developed by Gioia and Guilhardi (2018) in order to verify whether its tasks produce the target behaviors in children out of risk for ASD. Eight participants aged between 12 and 24 months were included, from public daycare centers and private schools in the city of São Paulo, Brazil. A prospective longitudinal design was used. The tasks with the highest percentage in producing the target behaviors were: 9, 10 and 12, with a 100% rate; 2, 4 and 5, with 92.31%; and 3 and 1, with 84.62% and 76.92%, respectively. The tasks that obtained the lowest percentage in producing the target behaviors were: 8, with 61.54%; 11, with 33.33%; 6, with 15.38%; 7, with 7.69%; and 13, which did not produce the target behavior at all. The most frequently observed accompanying behavior was the eye contact, while smiling/laughing, and babbling appeared less frequently. The main limitations of this study were a short follow-up/application of the protocol as well as a reduced number of participants